Protocol for a scoping review of older informal carers and digital health service use - Emanuela Sala; Federica Cretazzo (BMJ Open)
Introduction The ageing population and increasing demands for healthcare pose challenges for national health services, which are increasingly looking to digital health services (DHS) as a potential solution. However, older informal carers, who provide unpaid care, often lack the digital skills necessary to access and use DHS, placing them at risk of social exclusion. This scoping review aims to systematically map and explore the existing literature on this topic, with the goal of identifying and addressing gaps in the research.Methods and analysis This scoping review follows Arksey and O'Malley’s methodological framework. A systematic search will be conducted across seven databases: AgeLine, PubMed, ScienceDirect, Scopus, Social Sciences Abstracts, SocINDEX and Web of Science, focusing on studies published in English from 2010 onwards. The research team will collectively work on all stages of the review, ensuring consistency and collaboration throughout. Data extraction will capture key information on study topics, participant demographics, types of DHS and study design. The findings will be analysed using descriptive statistics.Ethics and dissemination Ethical approval is not required for this scoping review as it will rely solely on previously published data. The findings will be disseminated through peer-reviewed publications, conference presentations and engagements with non-academic stakeholders through seminars and workshops to maximise societal impact.